Additively manufactured aluminium nested composite hybrid rocket fuel grains with breathable blades - Dandan Qu; Xin Lin; Kun Zhang; Zhiyong Li; Zezhong Wang; Guoliang Liu; Yang Meng; Gengxing Luo; Ruoyan Wang; Xilong Yu (Virtual and Physical Prototyping, 2023)
Hybrid rocket engines suffer from the restricted mechanical properties and low regression rates of current polymeric fuel grains. We propose a three-dimensional printed aluminium (Al) nested composite fuel grain with millimetre-scale lattice pores (referred to as Al-L). In this study, breathable Al blades with micrometer-scale interconnected pores (Al-B) and blades combining millimetre-scale and micrometer-scale pores (Al-B&L) are designed. The formation mechanisms, characteristics, and effects of the breathable blades are analysed in simulations, micro-computed tomography, and cyclic compression tests. The mechanical properties of the composite fuel grains are investigated numerically and in compression tests. Al-B has the highest Young’s modulus at more than 15 times that of a paraffin-based fuel grain and Al-B&L has the highest yield stress at 4 times that of the paraffin-based fuel grain. Referring to combustion properties, the regression rates of the Al-B and Al-B&L grains are respectively 63.3% and 58.2% greater than the regression rate of the paraffin-based fuel grain.